KEMISKINAN DAN SOLUSI PENGENTASAN KEMISKINAN PERKOTAAN DI INDONESIA - Hasmin Hasmin (AkMen JURNAL ILMIAH, 2011)
Poverty is a global problem which is also a problem we all, but must be addressed with the methods and means that must be tailored to local circumstances as not all methods fit the local circumstances of each region. The perception of poverty will have a big impact on poverty reduction. So far we only see it from the standpoint of poverty is measured as low income; job hereditary non-permanent and without skill; slum dwellings, narrow, dense, and extended family in one house; and grouped with other poor people refers to the similarity between them. Such a view gives rise to all the policies that existed during this and the result is still not yet maximum, therefore it needs a new vision to transform poverty. We propose a model of poverty reduction with reference to how to change the factors of poverty that exist in that person's own poor before granting the drivers from the outside, so to minimize the factors present in the poor is expected to change towards the better will be achieved.